Adjusting vehicle characteristics by means of driver models. (4th August 2014) - Apel, A.; Mitschke, M.
Describing drivers' behaviour in lateral control, there are various approaches. Most of them use system theory to model the driver. The present knowledge shows that the driver can adapt to different vehicles. In addition to that, it is shown that drivers' behaviour varies with the driving situation. To find the basics of that adaptation, a criterion for description of the driver is required that remains constant with variations of the vehicle and the driving situation. With the help of that criterion, the amount of driver's adaptation is shown depending on variations of the vehicle. Predictions can be made with the vehicle ratings by real drivers, which evaluate the driving performance of vehicles using driver models.